The "third abstraction" of the Chinese artist LaoZhu: Neural and behavioral indicators of aesthetic appreciation. Issue 2 (June 2017) - Bao, Yan; Yang, Taoxi; Zhang, Jinfan; Zhang, Jiyuan; Lin, Xiaoxiong; Paolini, Marco; Pöppel, Ernst; Silveira, Sarita
Abstract: The eminent Chinese artist LaoZhu has created a homogeneous set of abstract pictures that are referred to as the "third abstraction." By definition, these pictures are meant to be representations of the artist's personal involvement and as such to create an internal point of view in the observer on an implicit level of processing. Aiming at investigating whether the artist's choice of a specific color is experienced in a specific way in the recipient, we assessed both explicit and implicit (i.e. neurocognitive) correlates in naive viewers of LaoZhu's pieces. The behavioral results reveal a preference of the original red paintings over color‐changed counterparts in green or black. Paradoxically and inconsistent with predictions, we found higher levels of neural activation in several brain regions (predominantly in the frontal and parietal cortices) for the color‐changed compared to the original red conditions. These observations add empirically to the complementarity of early visual pathways and higher‐order cognition as well as of explicit and implicit information processing during aesthetic appreciation. We discuss our findings in light of processing effort and top‐down control of the color‐changed paintings. With regard to the third abstraction as defined by LaoZhu, in particular to the distinction between an external and internal point of view when viewing abstract art, our results contribute to an understanding of "abstraction and empathy" as a fundamental part of aesthetic appreciations.